The advantages and disadvantages of microcredit The case of Chile - Bellon, Fotis; Gutiérrez Chvalkovská, Jana; Inostroza Pino, Luis Ernesto; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
The aim of this thesis is to contribute to the debate on microfinance commercialization, using the case of Chile. Another purpose of this thesis consists in mapping the field of microfinance in Chile. The hypothesis that is examined in this study is whether the commercialization of microfinance in Chile has brought opportunities and trade-offs with respect to poverty alleviation in the country. The methodology used in order to gain understanding of several aspects of commercialization of the microfinance sector in Chile is descriptive statistics accompanied by a qualitative analysis of the demand side of microfinance. To this end, interviews were conducted with several microfinance institutions and specialists. The results of the study indicate that the commercialization of microfinance in Chile has indeed brought opportunities and trade-offs with respect to poverty alleviation in Chile. Two opportunities that this study defines, are the increase in the scale of outreach and the increase of geographical outreach. Secondly, in contrast to these opportunities, a tendency for the commercialized microfinance institutions to pay less attention to the poorest segment of the Chilean population, is defined as a trade-off of the commercialization of microfinance.
Vedoucí práce: Jana Gutiérrez Chvalkovská
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses